2023
DOI: 10.3389/fmed.2023.1132476
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and survival in nonagenarians during the COVID-19 pandemic: Unstable equilibrium of aging

Abstract: IntroductionAging puts the human body under an immense stress and makes it extremely susceptible to many diseases, often leading to poor outcomes and even death. Long-living individuals represent a unique group of people who withstood the stress of time and offer an abundance of information on the body’s ability to endure the pressure of aging. In this study, we sought to identify predictors of overall one-year mortality in 1641 long-living individuals. Additionally, we analyzed risk factors for COVID-19-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Advancing age leads to several clinical and epidemiological differences between young and elderly patients. Even among the elderly, age groups should be considered in the patient's clinical management, since studies have shown differences in clinical profile and outcomes when comparing different age groups among patients aged 60 or older [9][10][11] In the studied group, there was a high prevalence of CKD patients (40%). Published studies suggest that these patients have a higher incidence of AKI 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Advancing age leads to several clinical and epidemiological differences between young and elderly patients. Even among the elderly, age groups should be considered in the patient's clinical management, since studies have shown differences in clinical profile and outcomes when comparing different age groups among patients aged 60 or older [9][10][11] In the studied group, there was a high prevalence of CKD patients (40%). Published studies suggest that these patients have a higher incidence of AKI 12 .…”
Section: Discussionmentioning
confidence: 99%
“…These factors might act as competitive confounders in an observational study or mediating factors in a MR study. Cognitive impairment, frailty and other aging-associated diseases had the potential to serve as candidate factors ( 47 , 48 ). On the basis of these observations and our MR results, we highlighted that older people should pay more attention to prevention, diagnosis, and treatment of SP instead of specific interactions between COVID-19 and SP, which would make it easier to break the dangerous vicious cycle and improve quality of life.…”
Section: Discussionmentioning
confidence: 99%